A short overview on practical techniques for protein crystallization and a new approach using low intensity electromagnetic fields. Issue 1 (February 2022) - Campos-Escamilla, Camila; Gonzalez-Rámirez, Luis A.; Otálora, Fermín; Gavira, José Antonio; Moreno, Abel
Abstract: This contribution deals with a practical overview of some popular and sophisticated crystallization methods that help increase the success rate of a crystallization project and introduces a newly developed method involving low intensity electromagnetic fields. Aiming to suggest a methodology to follow, the present contribution is divided into two main parts in a logical order to get the best crystals for high resolution X-ray crystallographic analysis. The first part starts with a short review of the chemical and physical fundamentals of each crystallization method through different strategies based on physicochemical approaches. Then, practical non-conventional techniques for protein crystallization are presented, not only for growing protein crystals, but also for controlling the size and number of crystals. These include crystal growth in gels, counter-diffusion, seeding, and macromolecular imprinted polymers (MIPs). The second part shows the effects of coupling low intensity electric fields (in the scale of units of  μAmperes) with weak magnetic fields (in the scale of milli Tesla) applied to protein crystallization. This approach consists of a novel experimental set up, which was used to study the influence of the coupled fields on the crystallization of lysozyme in solution and in gel media. This new approach is based on the classical theories of transport phenomena and offers a more accessible strategy to obtain suitable crystals for X-ray characterization or Neutron diffraction investigations. Graphical abstract: Image, graphical abstract